THE OFFENSE OF SHARING ELECTRONIC DOCUMENT DISSEMINATING ELECTRONIC DOCUMENTS CONTAINING DEFAMATORY INFORMATION - Harahap, Faisal Sadat Soaduon; Siregar, Dahris; Na’im, Khairun; Sitepu, Karolina (Al-Adl : Jurnal Hukum, 2024)
The rapid development of information technology has raised concerns about cybercrime and mayantara crime, which has an impact on various aspects of life. Therefore, people who communicate on social networks must have good ethics and interact well with others because their mistakes can result in criminal sanctions. This research aims to understand criminal offenses, sanctions, and legal considerations in the dissemination of defamatory electronic documents and information. Normative juridical is used by the author in this research which means using court decisions as the basis for solving problems. Secondary data is obtained from primary data used in this research. Data for this research was collected through literature research. Qualitative data was used for analysis. Dissemination of electronic information containing defamation or Article 27 paragraph (3) of the Electronic Information and Transaction Law regulates defamation. Defamation of private electronic information is a violation of the law. In Decision No. 978/Pid.Sus/2018/PT. MDN of the Medan High Court, the judge decided that the perpetrator of the criminal offence of disseminating electronic documents and information containing insults and defamation fulfilled the requirements of Articles 45 and 27 of the Electronic Information and Transaction Law, both including paragraph (3). This research concludes that the judge has applied the provisions of the Electronic Information and Transaction Law. Future research should conduct field research related to this field.